2012
DOI: 10.1177/0040517512461707
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of textile fabrics under various thermal exposures

Abstract: This study explores the behavior of textile fabrics under thermal exposures. The performance of thermal protective textile fabric systems with different structural features was evaluated under laboratory simulated thermal exposures. The study demonstrated that the protective performance of textile fabric systems varies with different types of thermal exposure. To provide effective protection in flame and radiant-heat exposures, the most important fabric properties to address are emissivity, absorptivity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
130
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(130 citation statements)
references
References 25 publications
(46 reference statements)
0
130
0
Order By: Relevance
“…Impermeable fabrics have been shown to offer the highest protection against hot liquids, with semi-permeable fabrics offering better protection than permeable fabric systems (Jalbani et al 2012;Lu et al 2013a;. Mandal et al (2013) reported that fabric thickness was positively correlated with predicted time to second degree burn injuries from hot water, yet air permeability of the fabric system had a greater influence (Mandal et al 2013). Air permeability has also been noted to be important in other studies, where fabrics with higher air permeability offered lower protection against hot liquids Jalbani et al 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Impermeable fabrics have been shown to offer the highest protection against hot liquids, with semi-permeable fabrics offering better protection than permeable fabric systems (Jalbani et al 2012;Lu et al 2013a;. Mandal et al (2013) reported that fabric thickness was positively correlated with predicted time to second degree burn injuries from hot water, yet air permeability of the fabric system had a greater influence (Mandal et al 2013). Air permeability has also been noted to be important in other studies, where fabrics with higher air permeability offered lower protection against hot liquids Jalbani et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…There have been several studies investigating the performance of various permeable, semi-permeable and impermeable fabrics and garments used in high-risk industries (e.g., oil and gas, fire-fighting), where flame retardant protective apparel is essential but hot water and steam hazards can also be present (e.g., Jalbani et al 2012;Lu et al 2013aLu et al , 2015aMandal et al 2013). Impermeable fabrics have been shown to offer the highest protection against hot liquids, with semi-permeable fabrics offering better protection than permeable fabric systems (Jalbani et al 2012;Lu et al 2013a;.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] From the middle of the 20th century, the application of these sensors gained popularity in the textiles and clothing industry; notably, these sensors have been successfully employed to evaluate the thermal protective performance (TPP) of firefighters'/industrial-workers' clothing. [14][15][16][17] Statistics shows that more than 75,000 on-duty firefighter/industrial-worker burn injuries and fatalities occur every year in the USA, and these injuries are prevalent due to the inadequate performance of their protective clothing. [15][16][17][18][19][20][21][22][23][24][25][26] In this context, thermal sensors are used to predict the heat flux transferred through protective clothing under fire exposures; the heat flux predicted is used to evaluate the performance of protective clothing.…”
mentioning
confidence: 99%
“…[14][15][16][17] Statistics shows that more than 75,000 on-duty firefighter/industrial-worker burn injuries and fatalities occur every year in the USA, and these injuries are prevalent due to the inadequate performance of their protective clothing. [15][16][17][18][19][20][21][22][23][24][25][26] In this context, thermal sensors are used to predict the heat flux transferred through protective clothing under fire exposures; the heat flux predicted is used to evaluate the performance of protective clothing. [14][15][16][17]25,26 In the last few decades, many thermal sensors have been developed by considering numerous features (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation